2005
DOI: 10.1523/jneurosci.4787-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Development of Electrical and Chemical Synaptic Connections Generates a Specific Behavioral Circuit in the Leech

Abstract: Neuronal circuits form during embryonic life, even before synapses are completely mature. Developmental changes can be quantitative (e.g., connections become stronger and more reliable) or qualitative (e.g., synapses form, are lost, or switch from electrical to chemical or from excitatory to inhibitory). To explore how these synaptic events contribute to behavioral circuits, we have studied the formation of a circuit that produces local bending (LB) behavior in leech embryos. This circuit is composed of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 69 publications
2
33
0
Order By: Relevance
“…Our experiments revealed that the circuit is formed first by electrical synapses at the stage when touching an embryo generates CI (Eisenhart, 2000;Marin-Burgin et al, 2005. Chemical synapses, including inhibitory connections, appear later in development, modifying this circuit that initially includes only electrical connections.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Our experiments revealed that the circuit is formed first by electrical synapses at the stage when touching an embryo generates CI (Eisenhart, 2000;Marin-Burgin et al, 2005. Chemical synapses, including inhibitory connections, appear later in development, modifying this circuit that initially includes only electrical connections.…”
Section: Introductionmentioning
confidence: 82%
“…There are, however, a few animals in which specific neuronal circuits are well understood at the level of each participating identified neuron and its connections (Marder and Calabrese, 1996;Kristan et al, 2005;Marder et al, 2005;Katz, 2007), and some laboratories are beginning to look closely at how those circuits are established during development (Casasnovas and Meyrand, 1995;Fenelon et al, 1999;Le Feuvre et al, 1999;Kristan et al, 2000;Marin-Burgin et al, 2005.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is becoming clear that interplay between electrical and chemical modes of neural communication have important impacts on neural network formation. The formation of specific neural circuits in leech embryos involves the development of inhibitory, GABAergic connections that shape pre-existing electrical synaptic connections (Marin-Burgin et al, 2005;Marin-Burgin et al, 2006). Interestingly, most electrical synapses in the juvenile neocortex on mammals couple inhibitory networks of GABA-ergic interneurons (Galarreta and Hestrin, 1999;Gibson et al, 1999;Hestrin and Galarreta, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Axonal pathfinding and growth cone-cell/substrate interactions have been studied extensively in the embryonic leech because its large, identified cells allow for intracellular recordings and injections with dye, even in early embryos (Kuwada, 1985;Wang and Macagno, 1997;Baker at al., 2003;Marin-Burgin et al, 2005). One uniquely accessible peripheral cell in the embryo is the comb cell (CC).…”
Section: Indexing Terms: Pathfinding; Development; Filopodial Retractmentioning
confidence: 99%